Summer distribution and ecological role of seabirds and marine mammals in the Norwegian and Greenland seas (June 1988) - Joiris, Claude (1992)
During the ARK V /2 expedition of RV Polarstern in the Norwegian and Greenland seas in June 1988, 380 half hour counts for marine vertebrates (seabirds, pinnipeds and cetaceans) were carried out. Results are presented as total numbers encountered and then converted into density and food intake. Mean food intake was 2.2 kg fresh weight per km2 per day for seabirds, with a higher value in Atlantic water (2.5) lower values in polar water and the pack ice (1.7 and 1.9), and an intermediate value at the ice edge. The main species were the alcids (1.5, primarily Little Auk, Alle alle and Brünnich's Guillemot, Urea Iomvia),the Fulmar, Fulmarus glacialis (0.5), and the Kittiwake, Rissa tridactyla (0.2). The ecological role of cetaceans was clearly lower, with a mean value of 0.2 and a maximum of 0.7 in Atlantic water (rough evaluation, due to the low number of contacts). The food intake by pinnipeds was 0.55 kg/km2 day at the ice edge and 0.4 in the pack ice; they were mainly harp, Phoca groenlandica and hooded seals, Cystophora cristata, in one main concentration each and ringed seals, Phoca hispida, scattered on the pack. Data for July 1988 show a great similarity with these results, except for a lower density of alcids, which probably reflects that Little Auk, Brünnich's Guillemot and Common Guillemot, Uria aalge already had started to leave the region. © 1992. SCOPUS: ar.j info:eu-repo/semantics/published